Germinations 7 : Biennale Européenne des jeunes artistes. - Magasin-Centre National d'Art Contemporain, Grenoble; Carignon, Alain; Dondelinger, Jean; von Fürstenberg, Adelina (Grenoble : Magasin - Centre National d'Art Contemporain, 1992)
Heynen, Günther ; Docte, Philippe Le ; Verbouwe, Ann ; Bommert, Jens ; Frommherz, Gerlinde ; Leu, Anja ; Neumann, Wolfram ; Paesler, Susanne ; Ritter, Wolfgang ; Simon, Monika ; Verbeek, Jan ; Imrova, Xénia ; Juzova, Irena ; Mica, Vojtech ; Ondák, Roman ; Brinch, Jes ; Holst Henckel, Peter ; Petersen, Lars Bent ; Rössell, Peter ; Perujo, Isidro Blasco ; Canogar, Daniel ; Frances, Alex ; Ges, Marcel ; Fontanals, Toni Giro ; Etxeberria, Pello Mitxelena ; Pradas, Mau Monleon ; Muinelo, Oscar ; Barbier, Gilles ; Duchatelet, Caroline ; Houillier, Sydney ; Lelong, Laurent ; Manche, Mathieu ; Moriceau, Laurent ; Mroivili, Ali ; Salavert, Aurélie ; Buet, Emma ; Cooley, Anna ; Fahy, Katie ; Lane, Esther ; Persaud, Niall ; Pratt, Katie ; Smith, Philip ; Thompson, Laura ; Argyrou, Michael ; Criparacos, Dominique ; Palaska, Aliki ; Xanthakis, Alexandros ; Durcan, Sarah ; Mulligan, Lee ; Beöthy, Balázs ; Gal, Andras ; Köves, Eva ; Takacs, Mate ; Baerveldt, Sharon ; Lamers, Kiki ; De Rooy, Noor ; Sloots, Karin ; Gomulicki, Maurycy ; Sosna, Miroslaw ; Szczepanski, Zbigniew ; de Barros, Ana Sofia Namora Quintino ; Queiroz, Joao Paulo Gomes de Araujo
bibliografie
biografie
Germinations 7, Magasin - Centre National d'Art Contemporain, Grenoble, 20.12.1992 - 24.01.1993
Frans & Duits & Engels
boek